Personality correlates of the social anxiety - Karaś, Aneta (Studia Psychologica: Theoria et praxis, 2006)
The work is empirical in character and concerns findings the relationship between the social anxiety and the personality. The research group consisted of 60 students (30 women and 30 men), aged 20-26. The following techniques were used: The Adjective Check List Manual of G.H. Gough, A.B. Heilbrun; State-Trait Anxiety Inventory (STAI) of C.D. Spielberger, R.L. Gorusch, R.E. Lushene; the subscale X1 of STAI modified to measurement of the social anxiety; Social Anxiety Scale designed by authoress of this article. The analysis of the study has shown that the tendency to feel social anxiety correlate moderately with some aspects of self-concept. The hypothesis concerning relation between the social anxiety and the global self-esteem was not confirmed. However, the self-concept of high socially anxious individuals in the sample is characterized by specific differences between real ego and ideal ego.